Potential Effects of Climate Change on the Productivity of U.S. Dairies. (25th February 2014) - Key, Nigel; Sneeringer, Stacy
Abstract: In the United States, climate change is likely to increase average daily temperatures and the frequency of heat waves, which can reduce meat and milk production in animals. Methods that livestock producers use to mitigate thermal stress—including modifications to animal management or housing—tend to increase production costs. We use operation-level economic data coupled with finely-scaled climate data to estimate how the local thermal environment affects the technical efficiency of dairies across the United States. We then use this information to estimate the possible decline in milk production in 2030 resulting from climate change-induced heat stress under the simplifying assumptions that the production technology, location of production, and other factors are held constant. For four climate model scenarios, the results indicate modest heat-stress-related production declines by 2030, with the largest declines occurring in the southern states.